2018
DOI: 10.1002/ente.201800385
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Germanium as an Efficient Auxiliary Pre‐Dopant in Carbon Nanotubes on Enhancing Oxygen Reduction Reaction

Abstract: In this study, sulfur‐doped carbon nanotubes with germanium as a pre‐dopant (SGe‐CNTs) are successfully prepared by sequential doping of germanium and sulfur, and their activity oxygen reduction reaction (ORR) activity is evaluated. As comparison, Ge‐doped CNTs and S‐doped CNTs are synthesized. The electrochemical results reveal that both Ge‐doping and S‐doping could improve the ORR activity of CNTs. In the synthesis process of SGe‐CNTs, germanium is deemed to be an efficient auxiliary pre‐dopant, since german… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Figure j–l shows the fitted XPS plots for Pd 3d, Ge 3d, and Pt 4f edges, respectively, of Pt 0.2 Pd 1.8 Ge. It validates the presence of Pd, Ge, and Pt in metallic states at binding energies of 335.46, 28.92, and 71.49 eV with a slight presence of PdO, GeO and GeO 2 , and Pt oxides, respectively, on the surface due to surface oxidation . It can be concluded that after substitution, Pt stays in a slightly higher oxidation state with a decrease in the Pd oxidation state.…”
Section: Results and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Figure j–l shows the fitted XPS plots for Pd 3d, Ge 3d, and Pt 4f edges, respectively, of Pt 0.2 Pd 1.8 Ge. It validates the presence of Pd, Ge, and Pt in metallic states at binding energies of 335.46, 28.92, and 71.49 eV with a slight presence of PdO, GeO and GeO 2 , and Pt oxides, respectively, on the surface due to surface oxidation . It can be concluded that after substitution, Pt stays in a slightly higher oxidation state with a decrease in the Pd oxidation state.…”
Section: Results and Discussionsupporting
confidence: 78%
“…It validates the presence of Pd, Ge, and Pt in metallic states at binding energies of 335.46, 28.92, and 71.49 eV with a slight presence of PdO, GeO and GeO 2 , and Pt oxides, respectively, on the surface due to surface oxidation. 29 It can be concluded that after substitution, Pt stays in a slightly higher oxidation state with a decrease in the Pd oxidation state. This signifies that charge transfer from Pt to Pd takes place, which backs up the observation obtained from XANES analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are many non‐Pt‐based catalysts [8–12] that have been studied, such as transition metal‐based catalysts [13–17] and heteroatom‐doped carbon‐based catalysts [18–22] . Among them, heteroatom‐doped carbon‐based materials with obvious advantages of high conductivity, good durability and excellent activity have attracted considerable attention in recent years [23] . The synergistic construction of heteroatom co‐doping and generating hierarchical architecture is regarded as one of the most promising methods for achieving outstanding ORR carbon materials [24–26] .…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Germanium (Ge), as one kind of semiconductor materials, has been proved to be an effective heteroatom to enhance the catalytic activity of carbon nanotube (CNT) toward ORR. 47,48 The co-doping of Ge and nitrogen, sulfur, or phosphorus into CNT exhibits outstanding activity for ORR compared with solely heteroatom-doped CNT. The improved performance is due to the fact that the doping of Ge could change the electronic and physical properties of carbon materials, resulting in the improvement in ORR performance.…”
Section: Introductionmentioning
confidence: 99%